2013
DOI: 10.1523/jneurosci.3473-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

CGRP Inhibits Neurons of the Bed Nucleus of the Stria Terminalis: Implications for the Regulation of Fear and Anxiety

Abstract: The bed nucleus of the stria terminalis (BNST) is thought to generate anxiety-like states via its projections to autonomic and neuroendocrine regulatory structures of the brain. However, because most BNST cells are GABAergic, they are expected to inhibit target neurons. In contrast with this, infusion of calcitonin gene-related peptide (CGRP) into BNST was reported to potentiate anxiety while activating BNST targets. The present study aimed to shed light on this paradox. The CGRP innervation of BNST originates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
0
26
1
Order By: Relevance
“…In relation to anxiety-related behavior, previous study indicated that CGRP potentiates anxiety-related behavior. 30 If the DKT acts on the colorectum through CGRP release, DKT increases anxiety-related behavior, but the effects were not observed in our study. Also, one previous study indicated that CGRP did not affect anxiety-related behavior estimated by EPM.…”
Section: Cgrpcontrasting
confidence: 73%
“…In relation to anxiety-related behavior, previous study indicated that CGRP potentiates anxiety-related behavior. 30 If the DKT acts on the colorectum through CGRP release, DKT increases anxiety-related behavior, but the effects were not observed in our study. Also, one previous study indicated that CGRP did not affect anxiety-related behavior estimated by EPM.…”
Section: Cgrpcontrasting
confidence: 73%
“…Vertebrate CGRP has been implicated in controlling anxiety [65, 66] and stress response [67, 68]. While not previously addressed experimentally, the intimate relationship between stress, anxiety, and sleep [5] suggest that CGRP might regulate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Based on findings from a recent study [95•], CGRP is likely to contribute to migraine pathology by facilitating anxiety-like states mediated via projections of the bed nucleus of the stria terminalis to autonomic and neuroendocrine regulatory structures of the brain. Injection of CGRP was shown to potentiate anxiety-like behaviors and increase neural activity in bed nucleus of the stria terminalis targets.…”
Section: Migraine Risk Factors and Cgrp: Role Of Stress Anxiety Andmentioning
confidence: 99%